Recommendations for Internal Communication to Strengthen the Employer Brand: A Systematic Literature Review - Santos, Sara (2023)
The increasingly intense competition in organisations means that they have to develop strategies to differentiate themselves. One of these strategies consists of using internal communication to improve the company’s attractiveness to outside talent and increase its attractiveness to its existing employees. However, this relationship still needs to be studied in the existing literature. This review aims to find and understand the main recommendations to be used in internal communication to improve employer branding. Nine open access scientific articles published between 2013 and 2023 on Scopus and Web of Science, written in English, met the inclusion criteria. Internal communication has been proven to play a crucial role in employer branding. The review presents a series of guidelines that can be incorporated into internal communication to strengthen the employer brand. These relate to communication qualities, knowing how to listen to and respect employees, maintaining responsiveness, providing feedback and the flow of company-related information, and choosing the appropriate communication channels. This study contributes to the ongoing scientific community by summarising and exploring the literature from the past decade. Its findings enhance our understanding of this field of study and strongly advocate for future research.